Synthesis, Characterization, and Biological Activitiy of Copper (II) Complexes Containing Bidentate Schiff Bases - Mihsen, Hayder Haimed (University of Thi-Qar Journal of Science, 2019)
Three ligands have been prepared by condensation of dithiooxamide with 2,4,5- trimethoxy benzaldehyde, 4- dimethylamino benzaldehyde and Vanailin. These ligands are named N,N- bis( 2,4,5 – trimethoxybenzalidene) dithiooxamide(LH1), N,N-bis(4-dimethylaminobenzalidene) dithiooxamide(LH2) and N,N-bis (vanaillidene) dithiooxamide(LH3), respectively. Complexes of LH1, LH2 and LH3 were prepared with 1:2 M:L molar ratio, with copper ion in the formulas [Cu(LH1)2(H2O)2] Cl2.H2O.0.5CH2Cl2, [Cu (LH2)2(H2O)Cl] Cl.H2O and [Cu (LH3)2(H2O)2] CL2.H2O. The ligands and their complexes have been characterized by IR, UV-Vis spectroscopy Magnetic, conductivity measurements, thermal analysis and atomic absorption technique. Biological activities of the Schiff bases and their metal complexes have been evaluated against two types of pathogenic bacteria (Escherichia coli and staphylococcus aureus ).